WAYS TO SOLVE NON-PAYMENT PROBLEMS - Sayfiddinov, Ilhom Fayziddinovich (Educational Research in Universal Sciences, 2023)
The article discusses the ways to overcome the problem of insolvency. It also discusses in detail the ways to overcome the problem of insolvency. Opinions and conclusions were formed on insolvency, macroeconomic stability, competitiveness of the national economy, investment environment, strengthening of payment discipline.